2009
DOI: 10.1097/tp.0b013e3181a5cf3f
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic Liver Transplantation: T-Tube or Not T-Tube? Systematic Review and Meta-Analysis of Results

Abstract: Our systematic review and meta analysis favor the abandonment of T-tubes in orthotopic liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 21 publications
1
51
1
7
Order By: Relevance
“…Considering the significant heterogeneity, we suggest that both groups have an equal risk of cholangitis. Our findings are in contrast to the conclusions drawn from the previous meta-analyses concerning overall biliary complications and cholangitis (Sotiropoulos et al, 2009). Our analysis added three new studies: one was an RCT with a high Jadad score and the other two were comparative studies, among which one had selection bias and the other had five cases of living donor liver transplantation in the group without T-tube.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Considering the significant heterogeneity, we suggest that both groups have an equal risk of cholangitis. Our findings are in contrast to the conclusions drawn from the previous meta-analyses concerning overall biliary complications and cholangitis (Sotiropoulos et al, 2009). Our analysis added three new studies: one was an RCT with a high Jadad score and the other two were comparative studies, among which one had selection bias and the other had five cases of living donor liver transplantation in the group without T-tube.…”
Section: Discussioncontrasting
confidence: 57%
“…However, this may be partly due to the presence of biliary complications other than those considered in our study. Peritonitis and hepatic artery thrombosis were evaluated in a previous metaanalysis (Sotiropoulos et al, 2009), which showed that peritonitis had a higher incidence rate in the group with a T-tube, while hepatic artery thrombosis did not significantly differ between the two groups. Since the new studies did not provide data about these complications, we did not include them in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, comparison of the pure rate of bile leaks is misleading, but one has to consider their clinical severity. However this is not the case in most (meta-)analyses (29,30). Moreover, leaks after T-tube removal lack severity and are easy to treat, since they do not appear in the critical phase early after LT.…”
Section: T-tube: Risk or Benefit?mentioning
confidence: 95%
“…After final placement, the opening is further narrowed by PDS 5/0 stitches. Two metaanalyzes found an increased risk for bile leaks if a T-tube is used (28,29). A newer metaanalysis found no overall differences in biliary morbidity but a lower rate of biliary strictures in patients with T-tubes (30).…”
Section: T-tube: Risk or Benefit?mentioning
confidence: 99%